A relação entre experiência e justificação epistêmica: conceitualismo e não-conceitualismo - Apolinário, Vinícius Francisco (2023)
The aim of this dissertation is to investigate the epistemic debate about the relation between sensory experience and empirical beliefs, that is, the discussion about how perceptual content relates to the content of beliefs. We conduct this analysis around the problem of the justification of empirical beliefs, based on two debates. One, of historical character, which provides the context for the debate, starting from the dispute between foundationalism and coherentism about the justification of knowledge. Another, of thematic character, in which conceptualists and non-conceptualists attempt to defend different positions on the nature of perceptual content and, based on this, its epistemological consequences. Our conclusion, having considered the main arguments mentioned in this debate, is in favor of the non-conceptualist thesis, more specifically, the scenario-content thesis as the appropriate model of perceptual content. On this basis, we consider that perception is a non-conceptual form of representation and does not need to maintain inferential relations with propositional attitudes; it is the basis of conceptual acquisition and development; it is a type of mental content shared by human adults and nonlinguistic creatures (infants and non-human animals); finally, it is a more informational rich kind of representation than conceptually structured states. We have suggested, finally, that the appropriate relationship between belief and perception is a non-inferential one. We proposed that the epistemic role of perception is to be the basis of application of empirical concepts, bringing non-conceptualism closer to epistemological externalism.